Cloning and characterization of the gene (farA) encoding the receptor for an extracellular regulatory factor (IM-2) from Streptomyces sp. strain FRI-5. - Waki, M (1997)
IM-2 is a butyrolactone autoregulator that controls production of blue pigment and nucleoside antibiotics in Streptomyces sp. strain FRI-5. An IM-2-specific receptor gene, farA, was cloned from strain FRI-5, and nucleotide sequencing revealed that the farA gene consists of 666 bp encoding a 221-amino-acid protein of 24.3 kDa with an NH2-terminal amino acid sequence identical to that of purified native receptor. Another gene, farX, encoding a homolog of AfsA of Streptomyces griseus, was present upstream of farA. The monocistronic nature of the farA transcript was shown by Northern blot hybridization, and the transcript level increased upon addition of IM-2. Recombinant FarA expressed in and purified from E. coli showed clear ligand specificity toward IM-2, with a dissociation constant (Kd) for [3H]IM-2-C5 of 18.2 nM. FarA showed high overall homology to BarA (virginiae butanolide receptor from S. virginiae) and ArpA (A-factor receptor from S. griseus). Sequence alignment of the three receptor proteins revealed that the NH2-terminal region containing a helix-turn-helix DNA binding motif was highly conserved. The DNA binding motif is common in procaryotic repressors of the TetR family, suggesting that all the Streptomyces autoregulator receptors may act as transcriptional repressors.